Granulomatous Lobular Mastitis Associated with Mycobacterium abscessus in South China: A Case Report and Review of the Literature - Ye-sheng Wang; Qi-wei Li; Lin Zhou; Run-feng Guan; Xiang-ming Zhou; Ji-hong Wu; Nan-yan Rao; Shuang Zhu (Case Reports in Infectious Diseases)
Mycobacteria, which are known as rapidly growing bacteria, are pathogens that are responsible for cutaneous or subcutaneous infections that especially occur after injection, trauma, or surgery. In this report, we describe a species of Mycobacterium abscessus that was isolated from a breast abscess in a patient who was previously diagnosed with granulomatous lobular mastitis (GLM). This current case is the first ever presented case of GLM associated with M. abscessus documented in South China. The case presentation highlights the role of M. abscessus in GLM. The association of M. abscessus and GLM is discussed and a summary of breast infection due to Mycobacteria is given.